3D geometric modeling for the Yanjinggou anticline in the Longmen Shan fold-and-thrust belt, China: Oblique thrusting kinematic implications. (1st August 2019) - Li, Zhigang; Zhang, Peizhen; Jia, Dong; Zheng, Wenjun; Sun, Chuang; Li, Yiquan; Almeida, Rafael; Chen, Wei; Li, Tao
Graphical abstract: Previous studies have proposed that the Eastern Tibetan Plateau underwent ∼E–W oblique crustal shortening, due to the eastward extrusion of the plateau since ∼5–2 Ma to present. However, the effects of the oblique thrusting on the three-dimensional (3D) fold morphology and kinematics in the front of the Longmen Shan fold-and-thrust belt are still poorly understood. We use 3D seismic data to produce five 3D geometric models and compare our results with structural models of the Yanjinggou anticline in the Longmen Shan fold-and-thrust belt, to investigate the effects of oblique thrusting on 3D fold evolution. The results show that regional oblique thrusting occurred within the LMS fold-and-thrust belt, resulting in rotation and a curved structural morphology, and suggest that this process may be applicable globally to both small- and regional-scale structures, as well as larger-scale orogenic belts in obliquely convergent settings. Highlights: The effects of oblique thrusting on 3D fold geometry and kinematics are investigated. The Yanjinggou anticline developed as a trishear fault-propagation fold with 1.2 km shortening. The Yanjinggou anticline was affected by oblique thrusting at an angle of 55°. Abstract: Three-dimensional (3D) subsurface seismic data acquisition and modeling are rarely undertaken; consequently, the complex effects of oblique thrusting on the 3D morphology and kinematics of folds are still poorly understood. We use 3D seismic data to produce five 3D geometric models and compare our results with structural models of the Yanjinggou anticline in the Longmen Shan fold-and-thrust belt, to investigate the effects of oblique thrusting on 3D fold evolution. 3D geometric modeling results reveal that oblique thrusting may cause fold asymmetry, vertical axis rotation, and a curved fold axis. 3D seismic interpretations and structural modeling suggest that the Yanjinggou anticline developed as a trishear fault-propagation fold and experienced a maximum shortening amount of 1.2 ± 0.1 km. The 3D structural and geometric models are consistent with paleomagnetic results, suggesting that the anticline was affected by oblique thrusting at an angle of 55° above a listric thrust fault with three fault ramps (19°, 30°, and 40°), causing the fold to rotate and develop a curved morphology. The integrated method used in this study to investigate the effects of oblique thrusting on 3D fold morphology and kinematics can be applied to regional oblique thrusting in the Longmen Shan and other fold-and-thrust belts worldwide.